2004
DOI: 10.1109/lpt.2004.835617
|View full text |Cite
|
Sign up to set email alerts
|

An Eight-Channel Demultiplexing Switch Array Using Vertically Coupled Active Semiconductor Microdisk Resonators

Abstract: Abstract-We demonstrate a 1.6-nm spectrally spaced eight-channel demultiplexer using active semiconductor microdisk resonators as a platform technology. Taking full advantage of the active microdisks, we are able to switch ON and OFF a resonator individually and tune the resonant wavelength as well by controlling the current injection levels. The use of active microdisks affords narrow spectral linewidth ( 0.15 nm), low insertion loss ( 2.5 dB), and distinct channel isolation ( 15 dB) for the demultiplexed out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Vertically coupled rings made through techniques such as wafer bonding, as shown in Figure 10.7 [33], have less stringent waveguide spacing tolerances than horizontally coupled rings with air gaps between coupled guides [14]. Although small-bend radii can have high-optical losses, the smallness of the disks or rings enable the dense channel spacing in the spatial domain.…”
Section: Multi-channel Ring Resonator Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertically coupled rings made through techniques such as wafer bonding, as shown in Figure 10.7 [33], have less stringent waveguide spacing tolerances than horizontally coupled rings with air gaps between coupled guides [14]. Although small-bend radii can have high-optical losses, the smallness of the disks or rings enable the dense channel spacing in the spatial domain.…”
Section: Multi-channel Ring Resonator Devicesmentioning
confidence: 99%
“…(a) Schematic of active micro-disk resonator vertically coupled to I/O bus lines and (b) micrograph showing top view of a fabricated eight-channel active micro-disk demultiplexer[33].…”
mentioning
confidence: 99%
“…Optical microring resonators have attracted considerable attention owing to their simple structure, compact size, and many applications in optical signal processing, communication, and active devices, such as optical filters, wavelength multiplexers, and lasers [1][2][3]. Planar waveguide microring resonators have been well developed, but suffer from larger connection-losses with fibers and higher cost.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, semiconductor microdisk cavities have attracted a lot of attention for applications in photonic integrated circuits due to their promising and versatile optical functions. The extensive studies and discussions with varied microdisk cavities had been reported including filter [1][2][3], demultiplexer [4,5], modulators [6,7] and lasers [8][9][10][11][12][13]. The type cavities with whispering gallery mode (WGM) became one of excellent candidates for compact semiconductor lasers for the chip scale integrated systems.…”
Section: Introductionmentioning
confidence: 99%